2013
DOI: 10.1111/aab.12040
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and biochemical aspects of sorghum resistance to anthracnose mediated by silicon

Abstract: The use of silicon (Si) in agriculture has attracted a great deal of interest from researchers because of the numerous benefits of this element to plants, especially when they are submitted to abiotic and/or biotic types of stress. The host's increased resistance to diseases, promoted by Si, is mainly associated with the deposition of this element in the tissues and the potentiation of defence mechanisms. However, the mechanisms involved in Si-mediated host resistance need to be further investigated. Thus, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
(51 reference statements)
1
21
0
1
Order By: Relevance
“…Sorghum leaves inoculated with Colletotrichum sublineolum and supplemented with Si showed high Si deposition on infection sites and fewer and smaller acervuli compared with the non-treated leaves. In addition, there was a higher concentration of plant defense enzymes, peroxidases and polyphenol, and anthocyanin in Si-treated leaves (Resende et al, 2013). The authors also reported the joint action of physical and biochemical barriers promoted by Si action, reducing C. sublineolum infection.…”
Section: Joint Action Of Physical Barrier and Biochemical Mechanismsmentioning
confidence: 86%
See 3 more Smart Citations
“…Sorghum leaves inoculated with Colletotrichum sublineolum and supplemented with Si showed high Si deposition on infection sites and fewer and smaller acervuli compared with the non-treated leaves. In addition, there was a higher concentration of plant defense enzymes, peroxidases and polyphenol, and anthocyanin in Si-treated leaves (Resende et al, 2013). The authors also reported the joint action of physical and biochemical barriers promoted by Si action, reducing C. sublineolum infection.…”
Section: Joint Action Of Physical Barrier and Biochemical Mechanismsmentioning
confidence: 86%
“…effect on disease reduction to the formation of both physical barriers, by deposition of Si (Sangster et al, 2001;Kim et al, 2002;Pozza et al, 2004;Carré-Missio et al, 2012b), and chemical barriers such as defense enzymes (Cherif et al, 1994;Fauteux et al, 2005;Cai et al, 2008;Shetty et al, 2011;Polanco et al, 2012). The joint action of these barriers in disease control in plants fertilized with Si was observed by Cai et al (2008) and Resende et al (2013). Moreover, silicon is reported to interfere with the absorption of essential nutrients to plants, including horizontal resistance to form barriers as the wax layer and the cell wall, among others (Pozza et al, 2007;Moraes et al, 2009;Botelho et al, 2005).…”
Section: Modes Of Silicon Action In Plant Disease Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Deposition of these substances interrupts the open channel network present in plant cell walls, thus contributing to more precise regulation between cellular and apoplasmic pathways for water, solutes and toxins (Ranathunge et al ., ). Apart from the aforementioned modifications, cell walls of plants may be also strengthened by silicon deposition (Resende et al ., ; Najihah et al ., ). However, its specific binding form and site in the plant cell wall are not completely elucidated (Guerriero et al ., ).…”
Section: Introductionmentioning
confidence: 99%